(untitled) (Global Journal of Management and Business Research, 2026)
Small and medium-scale enterprises (SMEs) are important players in Ghana’s economic growth but are often prone to financial volatility due to ineffective financial management systems. The study investigates the influence of budgeting control practices on financial performance of SMEs, guided by agency and goal-setting theories. Drawing on a crosssectional survey of 200 SMEs, four dimensions of budgetary control formal budgets, review frequency, participative budgeting, and variance analysis were examined. Findings show that formal budgets, regular review, and participative budgeting significantly influence financial performance, while variance analysis doesn’t significantly influence financial performance. Managerial capacity and firm size mediate the relationships. The research concludes that effective budgetary control increases profitability and sustainability and recommends capacity building and flexible budgeting models to improve SME financial management in Ghana.